2014
DOI: 10.1186/1880-6805-33-28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wearing sanitary napkins of different thicknesses on physiological and psychological responses in Muslim females

Abstract: BackgroundMenstruation is associated with significant unpleasantness, and wearing a sanitary napkin (SN) during menses causes discomfort. In addition, many Muslim women use a thick type of SN during menses due to the religious requirement that even disposable SNs be washed before disposal. Therefore, the objective of this study was to measure the physiological and psychological responses to wearing SNs of different thicknesses during menstruation and non-menstruation phases at rest and during physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Both hypotheses are tenuous, however, given that direct hormone assessment was not part of the present research design. Also notable is that the negative feelings observed during menstruation are perhaps linked to the physical act of bleeding and associated unpleasant symptoms, both physical and psychological (34,35). Furthermore, there is evidence suggesting that the type and size of feminine hygiene products used during menstruation may have contributed to these responses (34,35), although these specific variables were not considered within the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hypotheses are tenuous, however, given that direct hormone assessment was not part of the present research design. Also notable is that the negative feelings observed during menstruation are perhaps linked to the physical act of bleeding and associated unpleasant symptoms, both physical and psychological (34,35). Furthermore, there is evidence suggesting that the type and size of feminine hygiene products used during menstruation may have contributed to these responses (34,35), although these specific variables were not considered within the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Also notable is that the negative feelings observed during menstruation are perhaps linked to the physical act of bleeding and associated unpleasant symptoms, both physical and psychological (34,35). Furthermore, there is evidence suggesting that the type and size of feminine hygiene products used during menstruation may have contributed to these responses (34,35), although these specific variables were not considered within the current study. The finding of a significantly higher HR during the luteal phase aligns with findings from prior research (36–38).…”
Section: Discussionmentioning
confidence: 99%
“…Gynecologic concurrent infections were also associated with a significant increase in prevalence of HPV infections. Further studies are necessary to confirm the low to moderate associations observed with respect to genital infections due to pads [8][9][10].…”
mentioning
confidence: 99%